First Experience with Fluorescence in Pediatric Laparoscopy - Fernández-Bautista, Beatriz; Mata, David Peláez; Parente, Alberto; Pérez-Caballero, Ramón; De Agustín, Juan Carlos (European Journal of Pediatric Surgery Reports, 2019)
Background The use of intraoperative fluorescence images with indocyanine green (ICG) has recently been described as an aid in decision-making during surgical procedures in adults.We present our first experiences with different laparoscopic procedures performed in children using ICG fluorescence images.Material and Method We have used ICG fluorescence imaging technique in varicocele ligation, two nephrectomies, cholecystectomy, and one case of aortocoronary fistula closure. All procedures were performed through a minimally invasive approach. A high definition camera equipped with a visible infrared light source and gray-scale vision technology was used.After injection of ICG before or during the laparoscopic procedure, precise identification of vascular anatomy and bile duct architecture were easily identified. Fluorescence helped to assess blood flow from the spermatic vessels, define the variability of renal vascularization, and determine the precise location of the aortocoronary fistula. Biliary excretion of the ICG allowed the definition of the biliary tract.Conclusion Fluorescein-assisted images allowed a clear definition of the anatomy and safe surgical maneuvers during surgical procedures. The ICG imaging system seems to be simple and safe. Larger and more specific studies are needed to confirm its applicability, expand its indications, and address its advantages and disadvantages.
Keywords: indocyanine green; laparoscopy; fluorescence; thoracoscopy; minimally invasive surgery